Annual Report on Exchange Arrangements and Exchange Restrictions 2004. (Annual Report on Exchange Arrangements and Exchange Restrictions; 2004, 2004)
This 2004 Annual Report on Exchange Arrangements and Exchange Restrictions provides a detailed description of the exchange arrangements and exchange/trade restrictions of individual IMF member countries and Hong Kong Special Administrative Region, as well as Aruba and the Netherlands Antilles. The report highlights that the exchange rate of the kuna is determined in the foreign exchange market. The Croatian National Bank may set intervention exchange rates, which it applies in transactions with banks outside the interbank market to smooth undue fluctuations in the exchange rate.